Crystal Structure and Thermal Chemical Properties of 2-Anilino-3-Methyl-6-Dibutylaminofluorane - Ding, Cai-Feng; Tian, Bing-Qing; Li, Xue-Mei; Liu, Qing; Zhang, Shu-Sheng; Xu, Hong; Ouyang, Ping-Kai (Asian Journal of Chemistry, 2010)
The crystal structure of 2-anilino-3-methyl-6-dibutylaminofluorane has been determined by single crystal X-ray diffraction method. The molecules are linked by N1-H1A.....O3 intermolecular interactions into zig-zag chains. The packing is stabilized by dipole-dipole and van der Waals' forces. The title compound starts to decompose in the range of 300–480ºC.